2023
DOI: 10.3390/healthcare11030374
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Continuance Intention in Non-Face-to-Face Telemedicine Services: Trust Typology and Privacy Concern Perspectives

Abstract: As the COVID-19 pandemic progressed, the resulting demand for telemedicine services increased. This research empirically examines the role of trust, privacy concerns, and perceived usefulness in customer confirmation, satisfaction, and continuing intention in telemedicine. A typology of trust was employed to classify trust into three dimensions and explore the mediating role of the three dimensions of trust in the relationship between satisfaction, perceived usefulness, and continued intention. We also examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…(141,142) However, a few studies also highlight contradicting findings which are multifactorial and scenario-dependent. (143,144) Studies assessing the use of telehealth diagnostics have also shown promising results in India which are similar to other studies conducted globally. (127,145147) Our review also highlights the utility of digital health interventions in the overall education and skill training of HRH personnel.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(141,142) However, a few studies also highlight contradicting findings which are multifactorial and scenario-dependent. (143,144) Studies assessing the use of telehealth diagnostics have also shown promising results in India which are similar to other studies conducted globally. (127,145147) Our review also highlights the utility of digital health interventions in the overall education and skill training of HRH personnel.…”
Section: Discussionsupporting
confidence: 74%
“…Globally as well, multiple studies have reported similar positives (141,142). However, a few studies also highlight contradicting findings which are multifactorial and scenario-dependent (143,144). Studies assessing the use of telehealth diagnostics have also shown promising results in India which are similar to other studies conducted globally (127,(145)(146)(147).…”
mentioning
confidence: 53%
“…Platforms that are perceived as less trustworthy may trigger reactance and privacy concerns among users (Bleier & Eisenbeiss, 2015). It is also discovered that when users have privacy concerns, trust that is based on structural assurance plays a more positive role in their continued usage intention (Zhu et al, 2023).…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
“…To explore the opportunities, challenges, issues, and bottlenecks of integrating these tools (alone or interconnected) into the domain, this Special Issue [10] was initiated in May 2022, and was subsequently completed in January 2023. This Special Issue collected 17 contributions plus an editorial [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and covered a wide range of topics, including:…”
mentioning
confidence: 99%
“…Zhu et al [16] empirically investigated the role of faith, privacy fears, and observed helpfulness in client approval and ongoing intention in telehealth. The findings indicated that faith influenced the connection between subjective helpfulness and approval with ongoing intention.…”
mentioning
confidence: 99%